2022
DOI: 10.1177/1071181322661175
|View full text |Cite
|
Sign up to set email alerts
|

Manual Wheelchair Movement Performance Differences Between Older Adults with Earlier- and Later-in-Life Incidence

Abstract: Independent mobility is crucial for healthy aging. Although there are anticipated differences between older adults with earlier-in-life (EL) versus later-in-life (LL) incidence of mobility disability, the degree to which incidence periods impact performance within environments is unknown. While current evaluation methods rely heavily on subjective ratings, historically excluded populations are prone to underrepresent their own challenges. This paper describes an experiment comparing the assumed, perceived, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…To follow up a baseline study conducted towards investigation of intervention effectiveness, here we propose the introduction of our novel methods aimed at examining the intervention impact on internal task representation and thus ensuing motor actions (Tabattanon et al, 2022). This method has potential to create a basis towards informing future intervention design.…”
Section: Mixed Methods In Design Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…To follow up a baseline study conducted towards investigation of intervention effectiveness, here we propose the introduction of our novel methods aimed at examining the intervention impact on internal task representation and thus ensuing motor actions (Tabattanon et al, 2022). This method has potential to create a basis towards informing future intervention design.…”
Section: Mixed Methods In Design Studiesmentioning
confidence: 99%
“…If this trend extends to a larger population, then the interventions may be promising in aligning performance to bottom-up perception. The earlier baseline study suggested that some manual wheelchair users committed a higher number of errors but still perceived a comparable level of performance quality to those who did not commit as many errors (Tabattanon et al, 2022). Such a mismatch may lead to an underestimation of the necessary motor corrections required to perform at an expected level and consequently reduced safety and misapplied confidence.…”
Section: Motor Action and Bottom-up Performance Alignmentmentioning
confidence: 99%
See 1 more Smart Citation